Study of transmission velocity of primary wave (P-wave) in coal measure sandstone - Singh T.N.; Dubey R.K. (My University, 2025)
An attempt is made to determine the transmission velocity of P-wave and correlate with uniaxial compressive strength, modulus of elasticity, Poisson's ratio, and density of coal measure sandstone. The investigation infers that the velocity of P-wave increases with increase in uniaxial compressive strength, modulus of elasticity, and density, whereas the velocity of wave decreases with increase in Poisson's ratio. These trends in correlation between velocity of P-wave and some strength properties of coal measure sandstone may be due to its strong dependency on elasticity of the rocks which indirectly governs the compressive strength and Poisson's ratios. The density of rocks is found to depend on the mineral constituents also influencing the transmission velocity of wave.